RERPRESENTASI EMPATI DAN INTERAKSI SOSIAL PESERTA DIDIK KELAS V SD DALAM PEMBELAJARAN: STUDI ANALISIS KEBUTUHAN - Amelia Fitri; Seni Apriliya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the representation of empathy and social interaction among fifth-grade elementary school students in learning as part of a needs analysis for emotional literacy. This research employed a descriptive qualitative approach. Data were collected through classroom observations involving 58 fifth-grade students and interviews with one teacher and two students selected purposively. The research instruments consisted of observation and interview guidelines developed based on two dimensions of emotional literacy, namely empathy and social interaction. The data were analyzed through data reduction, coding, theme grouping, and meaning interpretation based on the research focus. The findings show that students’ empathy has begun to appear in learning activities, but it has not developed evenly. Students’ caring attitudes tended to be selective and were mostly shown toward peers with whom they had close social relationships. Social interaction in learning was also not yet optimal, as indicated by unequal participation in group discussions, domination by several students, and the tendency of some students to remain passive or interact only with certain peers. These findings indicate the need to strengthen emotional literacy in learning, particularly in the dimensions of empathy and social interaction. Therefore, elementary school learning needs to be designed more intentionally by integrating social-emotional aspects so that students can build more inclusive, active, and collaborative social relationships.